The Midland Railway its rise and progress : a narrative of modern enterprise - Williams, Frederick Smeeton, 1829-1886 ([s.n.], 1878)
This title is in three parts, covering the history of the development of the Midland Railway, the engineering and topography of the line, and the daily administration and maintenance of the network.